Figure 2 in Morphological and molecular analyses on Richtersius (Eutardigrada) diversity reveal its new systematic position and lead to the establishment of a new genus and a new family within Macrobiotoidea - Guidetti, Roberto; Rebecchi, Lorena; Bertolani, Roberto; Jonsson, Kjell Ingemar; Kristensen, Reinhardt Møbjerg; Cesari, Michele (Zenodo, 2016)
Figure 2. Richtersius coronifer (A–D) and Diaforobiotus islandicus (E–J). A, buccal–pharyngeal apparatus, with enlarged terminal portion (arrow) of the buccal tube (neotype) (Norway). B, buccal–pharyngeal apparatus (population from northern Italy 1). C, buccal–pharyngeal apparatus, with the dorsal thickening in the anterior portion of the buccal tube (arrow) (Sweden). D, buccal–pharyngeal apparatus (Greenland). E, F, lateral view of the claws on the second leg at different focus levels. The evident stalk system (arrow) and cuticular pores (arrowhead) on the leg are visible (Norway). G, buccal–pharyngeal apparatus (ventral view), with some strong, scattered round teeth in the buccal armature (arrow) (Italy). H, buccal–pharyngeal apparatus (dorsal view), with the large tooth (arrow) on the internal surface of the buccal tube (Norway). I, buccal–pharyngeal apparatus (lateral view) (Greenland). J, anterior portion of the buccal tube (enlargement of I), with the large tooth on internal surface (arrowhead) and the dorsal thickening (arrow) (Greenland). A, B, D–F, H: phase contrast; C, G, I, J: differential interference contrast. Scale bars = 10 µm. : Published as part of Guidetti, Roberto, Rebecchi, Lorena, Bertolani, Roberto, Jonsson, Kjell Ingemar, Kristensen, Reinhardt Møbjerg & Cesari, Michele, 2016, Morphological and molecular analyses on Richtersius (Eutardigrada) diversity reveal its new systematic position and lead to the establishment of a new genus and a new family within Macrobiotoidea, pp. 834-845 in Zoological Journal of the Linnean Society 178 (4) on page 840, DOI: 10.1111/zoj.12428, http://zenodo.org/record/5369103